Determining the Parameters of Tetrahedral Splittings in the A1- and A2-Type States of Molecules with Spherical Symmetry (T d or О h ); Russian Physics Journal; Vol. 60, iss. 10 - Raspopova N. I. Natalya Ivanovna; Sklyarova E. A. Elena Aleksandrovna; Aslapovskaya Yu. S. Yuliya Sergeevna; Kuznetsov S. I. Sergey Ivanovich; Maul K. (2018, 2018)
Title screen